PERLINDUNGAN HUKUM BAGI KREDITUR PEMEGANG HAK TANGGUNGAN TERHADAP SENGKETA AGUNAN YANG MENGAKIBATKAN BATALNYA PERJANJIAN KREDIT - Fransisca Kusuma Aryani; Gunawan Djajaputra (Jurnal Hukum Adigama, 2018)
The process of granting credit with the guarantee of Mortgage Rights experienced many obstacles, one of which is the cancellation of credit agreement due to a lawsuit from a third party. Examples of problems that will researchers take is a case between PT PNM as creditor and Erlinawati as a debtor. Erlinawati applied for credit to PT PNM and pledged SHM No. 1716 without her husband's agreement, Bagus Satriya. As time went by, Erlinawati could not fulfill its obligations as stipulated in the credit agreement, and then PT PNM sent a warning letter to Erlinawati. Good people who know the land and buildings of his property are used as a direct guarantee to file a lawsuit to the Blora District Court. The Blora District Court ruled that credit agreements and Deed of Mortgage Rights (APHT) are invalid and null and void. So far the legal protection for debtors who have sued from the other party on the guarantee given by the creditor has not been regulated specially in the legislation. The law only regulates bad debts and debt repayment through the execution process stipulated in the Law on Banking and Insurance Rights Act. Legal protection that creditor can use when obtaining a lawsuit from a third party is by using the general guarantees provided for in Articles 1131 and 1132 of the Civil Code.